Family Storytelling: Involving Caregivers in Promoting Successful Early Language and Literacy Development - Catherine Gutierrez-Gomez (Educational Considerations, 1999)
There is increasing evidence that reinforces the belief that having strong oral experiences prior to entering school is one of the predictors for later success in literacy learning.